Investigation of Fatigue Assessment Method for Glass Fiber Reinforced Composite Hull Structures Based on Stiffness Degradation - Kaiyan Li; Guanyi Gao; Guoqing Feng; Yaozhong Fan; Yiyang Han (Journal of Marine Science and Engineering)
A study was conducted on the fatigue assessment method for composite ship structures under complex marine environments, and a fatigue assessment method based on the principle of stiffness degradation was proposed. Fatigue tests were performed on the composite material of the target ship to obtain the stiffness degradation parameters under tension–compression loading. Four fatigue hotspot areas in the midsection of the hull were selected, and mesh refinement was applied to these locations to accurately capture the variations in stress gradients. The structural stress response transfer function was calculated, and the short-term and long-term distribution data of wave loads were obtained. Finally, the fatigue life of the target ship hotspots was predicted by combining spectral fatigue analysis with the stiffness degradation theory. The results indicate that the connection between the bulkhead stiffener and the inner bottom plate has the shortest fatigue life, and its dimensions were optimized.